Revisión bibliográfica sobre las bacteriocinas y su aplicación como bioconservante dentro de la industria alimentaria - Catagña Rodriguez, Robinson Patricio (2022)
ABSTRACT: Nowadays, pathogenic microorganisms in food has been a challenge for industry food and it deteriorates food and produce consumer problems such as infections and intoxications. For this reason, the present research project aimed to study bacteriocins and their application as a bio preservative within the food industry. This research was carried out through a bibliographic review applying PRISMA statement, which has 4 systematic steps that are: identification, screening, selection and inclusion of studies. The bactericidal effect of Nisin was analyzed, showing the prolongation of the useful life of the treated foods and the colonyforming unit’s reduction of the pathogenic microorganisms. In the same way, the reported in vitro inhibitory capacity of new bacteriocins against different microorganisms was studied in which Escherichia coli, Listeria monocytogenes and Staphylococcus aureus, demonstrating a high inhibition spectrum under different ranges of pH and thermo stability that would allow its application in different food. These bacteriocins features made them as a potential alternative to the chemical preservatives that are used today and thus solve a growing market trend in consuming products with natural ingredients. However, it is important to continue conducting studies to expand the variety of bacteriocins and promote its application.